Action, design and research - a logical data model - Henriques, T. (2020)
Developing Action and Design Research (ADR) interventions involves the application of a rigorous set of processes, and the production of explicit data to support the whole process, evidencing its base, intermediate, and final results. In a previous publication – based on empirical work, a comprehensive literature review, and the practice of its application teaching graduate students on qualitative research – a conceptual model for ADR has been developed. It has presented a tri-dimensional perspective, emergent from the Organization Development, Engineering and Science approaches, identifying its core processes and data. Based on that view, a high-level Process Meta-Model has been produced, detailing the main processes involved in ADR interventions and the associated data flows. Progressing within this structured line of research, the objective of this publication is to present a pragmatic approach to ADR main data structures – under the form of a high-level Data Model – evidencing the core data involved in the design, planning, development, and evaluation of this kind of initiatives. It includes the associated data structure diagram and the relevant details of the respective data components, which will act as researchers’ facilitators for documenting the whole process.